Silencing of the lncRNA H19 enhances sensitivity to X-ray and carbon-ions through the miR-130a-3p /WNK3 signaling axis in NSCLC cells - Xueshan Zhao (BMC, 2021)
Abstract Background The lncRNA H19 is believed to act as an oncogene in various types of tumors and is considered to be a therapeutic target and diagnostic marker. However, the role of the lncRNA H19 in regulating the radiosensitivity of non-small cell lung cancer (NSCLC) cells is unknown. Methods The expression profiles of lncRNAs in NSCLC were explored via transcriptome sequencing. CCK-8, EdU incorporation and clonogenic survival assays were conducted to evaluate the proliferation and radiosensitivity of NSCLC cells. Flow cytometry and Western blotting were conducted to measure the level of apoptosis. The binding relationship between the lncRNA H19 and miR-130a-3p was determined by a dual-luciferase reporter assay. A binding relationship was also identified between miR-130a-3p and With-No-Lysine Kinase 3 (WNK3). Results Expression patterns of lncRNAs revealed that the lncRNA H19 was upregulated in radioresistant NSCLC (A549-R11) cells compared with A549 cells. Knockdown of the lncRNA H19 enhanced the sensitivity of NSCLC cell lines to X-ray and carbon ion irradiation. Mechanistically, the lncRNA H19 serves as a sponge of miR-130a-3p, which downregulates WNK3 expression. The lncRNA H19–miR-130a-3p–WNK3 axis modulates radiosensitivity by regulating apoptosis in NSCLC cell lines. Conclusion Knockdown of the lncRNA H19 promotes the sensitivity of NSCLC cells to X-ray and carbon ion irradiation. Hence, the lncRNA H19 might function as a potential therapeutic target that enhances the antitumor effects of radiotherapy in NSCLC.